Former Child Soldiers Status: How the International Criminal Court Considers Its Significance in the Sentencing Process - Pananjung, Dino Panji; Poerana, Sigar Aji (Padjadjaran Journal of International Law, 2019)
AbstractIn armed conflicts, children are often kidnapped and forced to become child soldiers since it is relatively easy for them to be indoctrinated (by violence and threats) and taught to commit crimes, such as looting and murder. Disobeyed children and those who try to escape will be punished in the form of torture or even executed in front of other children soldiers as a deterrence lesson. After no longer serving as soldiers, as they are growing up, they are entitled a status of ?former? child soldiers. Due to their backgrounds, it is most likely that those ?former? child soldiers might still live in rebellious environments and even consistently commit serious crimes including international crimes under the jurisdiction of International Criminal Court (ICC). This research thus analyses how the status of ?former? child soldiers plays significant role as a mitigating factor of punishment in the case brought before the ICC. The practices of ICC demonstrate that it has never considered the historical background of perpetrators including their ?former? status as child soldiers when deliberates a sentencing. This is due to the fact that such considerations are not stipulated in the Rome Statute. This article argues that ICC may refer to other considerations beyond what are written in Rome Statute. Article 21(3) of the Rome Statute can be used as a legal basis to consider the ?former? child soldier status as a sufficient factor to mitigate the punishment.Keywords: Child Soldier, International Criminal Court, Mitigating Factor, Judgment and Sentencing. AbstrakDalam konflik bersenjata, anak seringkali diculik dan dipaksa menjadi tantara anak, mereka juga didoktrin paksa (melalui kekerasan atau ancaman) serta diajakan untuk melakukan kejahatan seperti menjarah dan membunuh. Mereka yang tidak menurut dan yang mencoba melarikan diri akan dihukum dengan disiksa di hadapan para tantara anak lainnya sebagai contoh agar tidak ditiru oleh anak lainnya. Mereka disebut ?mantan tantara anak? setelah tidak lagi menjadi tentara atau telah dewasa. Tidak menutup kemungkinan ketika dewasa mereka hidup dengan jiwa pemberontak dan melakukan kejahatan serius bahkan kejahatan internasional yang menjadi jurisdiksi Mahkamah Pidana Internasional. Penelitian ini membahas apakah Mahkamah Pidana Internasional mempertimbangkan riwayat seorang pelaku kejahatan internasional yang menjadi seorang mantan tentara anak untuk meringankan hukuman mereka. Hasil penelitian menunjukkan bahwa praktik Mahkamah Pidana Internasional tidak pernah mempertimbangkan latar belakang pelaku kejahatan internasional sebagai mantan tentara anak. Penelitian ini berkesimpulan bahwa seharusnya Hakim Mahkamah Pidana Internasional dapat menggunakan ketentuan diluar Statuta Roma berdasarkan pasal 21(3) untuk mempertimbangkan status mantan tentara anak sebagai factor peringan hukuman.Kata Kunci: Tentara Anak, Mahkamah Pidana Internasional, Faktor Peringan, Pemidanaan.